A STUDY OF STRUCTURE, CONDUCT AND PERFORMANCE OF RICE MARKETING IN YOBE STATE, NIGERIA - Lawal, A. A.; Ibrahim, H.I.; Adeola, S.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study explored the structure, conduct and performance of rice marketing in Yobe State, Nigeria. A multistage sampling technique was used to select 90 respondents among which include 37 rice wholesalers and 53 rice retailers. Data were collected through structured questionnaires and analyzed using descriptive statistics, Gini coefficient and net market margin analysis. The Gini coefficient analysis revealed that significant income inequality, especially among rice retailers. In the performance segment, retailers outperform wholesalers in profitability. Retailers earn ₦15260 per bag and return on investment of 0.11, which is higher compared to wholesalers who earn ₦4260 per bag with a return on investment of 0.3. The marketing efficiency of both retailers and whole sellers indicates excess profit with 111% and 103% respectively. The major constraints to milled rice marketing in the study area were price volatility (100%), low capital investment (93.33%), seasonality of supply (93.33%), insecurity (90%) and poor road network (60%). The study concludes that a degree of inequality exist among rice markers, the performance of rice marketing is good as indicated by the market efficiency of above 100% indicating excess profit while the market conduct indicates that price setting is driven by demand and supply forces. These findings underscore the urgent need for targeted interventions to enhance the efficiency, equity, and sustainability of the rice marketing in study area. Addressing these challenges can significantly boost the livelihoods of all stakeholders involved in the marketing activities.